2020
DOI: 10.3389/fphys.2020.01049
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Modulation During Acute High-Altitude Exposure in Rats

Abstract: Baroreflex (BR) control is critically dependent of sympathetic and parasympathetic modulation. It has been documented that during acute hypobaric hypoxia there is a BR control impairment, however, the effect of a natural hypoxic environment on BR function is limited and controversial. Therefore, the aim of this study was to determine the effect of acute High-Altitude exposure on sympathetic/parasympathetic modulation of BR control in normal rats. Male Sprague Dawley rats were randomly allocated into Sea-Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In our Research Topic, Lang et al showed that in hypertensive miners ( n = 10) high altitude was the main factor affecting cardiac autonomic modulation, independently of hypertension. Of note, apparently, the parasympathetic arm of the autonomic nervous system was more affected by high altitude, similar to previous observations ( Beltran et al, 2020 ). Importantly, Lang et al also showed that hypertension was associated with reduced physical performance independently from altitude reached with a higher respiratory frequency.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our Research Topic, Lang et al showed that in hypertensive miners ( n = 10) high altitude was the main factor affecting cardiac autonomic modulation, independently of hypertension. Of note, apparently, the parasympathetic arm of the autonomic nervous system was more affected by high altitude, similar to previous observations ( Beltran et al, 2020 ). Importantly, Lang et al also showed that hypertension was associated with reduced physical performance independently from altitude reached with a higher respiratory frequency.…”
Section: Introductionsupporting
confidence: 91%
“…Natural conditions, such as high altitude, high gravity, extreme pressures, radiation, cold, heat, salinity, oligotrophic, and others, are examples of stressful factors that challenge the physical and chemical limits at which life can persevere. Among higher organisms, physiological manifestations such as cardiorespiratory adjustments for oxygen homeostasis are adaptive strategies allowing humans to work and live at high altitudes ( Beltran et al, 2020 ; Mallet et al, 2021 ; Lang et al ). Along with this, some human activities are performed in severe environmental conditions, such as diving, and races during extreme heat and cold, among others, which demonstrate the human capacity to push their limits to be able to respond and adapt to conditions where human life would be a great challenge ( Arce-Alvarez, et al, 2021 ; Arce-Alvarez, et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, combining pharmacological inhibition of sympathetic and/or parasympathetic control of the heart, Siebenmann et al demonstrated reduced cardiac parasympathetic activity as the main mechanisms underlying the increase of resting heart rate in response to middle-term exposure to altitude hypoxia (Siebenmann et al, 2017 ). The same evidence was reported in rats, with a parasympathetic withdrawal after 24 h of exposure to 3,270 m above sea level (Beltrán et al, 2020 ). A few evidence exists about ethnic differences in the autonomic control of the cardiovascular response to altitude hypoxia; e.g., altered muscle sympathetic nerve activity and beneficial lower sympathetic vasoconstrictor activity have been suggested as beneficial hypoxic adaptations in Sherpas (Simpson et al, 2019 ).…”
Section: Introductionsupporting
confidence: 79%
“…Indeed, it can be supposed that, before the trek started, participants had greater arousal and stress with respect to bBC. After the base camp circuit, albeit participants were tested at the same altitude as bBC, the hypobaric hypoxia exposure, along with the physical conditioning, posed a high stressor on participants, determining a chronic sympathetic activation and parasympathetic deactivation, as previously reported (Siebenmann et al, 2017;Beltrán et al, 2020). Considering reduced cardiac parasympathetic activity as the main mechanisms underlying the increase of resting heart rate in response to middle-term exposure to altitude hypoxia (Siebenmann et al, 2017), and that HRV metrics could be considered more adequate in estimate parasympathetic, rather than sympathetic, dynamics (Fontolliet et al, 2018;Thomas et al, 2019), all in all, HRV can be considered effective in monitoring altitude effects on autonomic control of cardiac rhythms, when direct or more effective measures (such as microneurography) are harsh to implement.…”
Section: Discussionmentioning
confidence: 86%
“…Although this result appears to be influenced by a single subject displaying a large increase in MABP, it seems intriguing to speculate that baroreceptor activity might be involved in the regulation of CO in acute moderate hypoxia ( Figure 2 ). Baroreflex sensitivity (hypocapnia triggered) is usually reduced in acute hypoxia, potentially related to an insufficient CO elevation to compensate for the hypoxia-related loss in VO 2peak [ 18 , 19 ]. A sufficient CO increase was particularly prevented in individuals with higher (but normal) values of systemic BP (and BP changes from normoxia to hypoxia), likely due to enhanced baroreceptor activity and the associated reduction in sympathetic activation and cardiac output [ 20 ].…”
Section: Discussionmentioning
confidence: 99%